Olympic Games and Indigenous Peoples: Possible Change in Global Sport towards Indigenous Sovereignties? - Lívia Šavelková (Acta Universitatis Carolinae Studia Territorialia)
Indigenous peoples have appeared at the Olympic Games since the beginning of the twentieth century not only as participants of contemporary “human zoo” performances, but as competitors in regular sport disciplines. Since then, their presence at these mega-events has varied, in relation to local and transnational politics. Although the idea of sport as a tool for development and change has been widely spread through global NGOs and global events, such as the Olympics, sovereignty issues of Indigenous peoples in general remain unsolved. For decades, the International Olympic Committee (IOC) insisted on Rule 50, which banned any sort of political protest during the Olympic Games. Recently, some global sport federations have begun to challenge this rule of the IOC in solidarity with the anti-racist Black Lives Matter movement. This paper seeks to address two main questions: How and if does the presence of the Indigenous peoples shape these largest global sport international events and their organizers? Does the presence of Indigenous peoples at the Olympics lead to potential changes of Olympic discourses related to Indigenous sovereignties? The paper argues that the IOC keeps shaping how Indigenous identities are portrayed, even though Indigenous participants work towards gaining the recognition of Indigenous sovereignties in relation to the Olympic structures.